Redescription of Brachirus aspilos (Bleeker 1852), a senior synonym of four nominal species, with a note on the distribution of Dagetichthys marginatus (Boulenger 1900) (Pleuronectiformes: Soleidae) - Okamoto, Jo; Motomura, Hiroyuki (Zootaxa, 2021)
The poorly known sole Brachirus aspilos (Bleeker 1852) is redescribed on the basis of the holotype and 48 non-type specimens from Japan, Taiwan, Philippine, Singapore, Indonesia, Papua New Guinea, and Australia. The species is characterized by the following combination of characters: dorsal-fin rays 64–76 (mode 71), anal-fin rays 51–62 (56), pored scales on straight portion of lateral line 93–126 (118); vertebrae 41–44 (43); pectoral-fin rays 4–7 (6) and 4–7 (5) on ocular and blind sides, respectively; pelvic-fin rays 4–6 (5) and 4–5 (4) on ocular and blind sides, respectively; caudal-fin rays 13–15 (14); body slightly elongate, its depth 40.0–51.0 (mean 45.5)% SL; head length 16.1–23.9 (18.6)% SL; pectoral fin on ocular side longer than that on blind side, 5.3–7.6 (6.6)% SL and 4.0–6.0 (4.8)% SL, respectively; pelvic fin on ocular side longer than that on blind side, 4.9–7.4 (6.0)% SL and 4.3–7.5 (5.8)% SL, respectively; body depth below lateral line 21.7–27.1 (23.4)% SL; lips without labial papillae; eyes separated by scaled interorbital space; cycloid or weakly ctenoid scales on blind side; body on ocular side uniformly brown or grey with dark vermiculation, some small white blotches along dorsal- and anal-fin bases, or without remarkable pattern. Brachirus dicholepis (Peters 1877), B. heterolepis (Bleeker 1856), B. marmoratus (Bleeker 1853), and B. sorsogonensis (Evermann & Seale 1907), previously regarded as valid species, are all regarded as junior synonyms of B. aspilos. In addition, specimens previously reported as Dagetichthys marginatus (Boulenger 1900) from the western Pacific Ocean are re-identified as B. aspilos, the former species being considered restricted to South African waters.